2005
DOI: 10.1088/0963-0252/15/1/007
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic measurements of the electron temperature in low pressure radiofrequency Ar/H2/C2H2and Ar/H2/CH4plasmas used for the synthesis of nanocarbon structures

Abstract: This paper deals with optical emission spectroscopy studies of low pressure (0.1-0.5 Torr) capacitively coupled radiofrequency hydrocarbon/argon-rich plasmas used for the synthesis of nanocarbon structures. The main goal of this paper is to obtain the electron temperature of such far-from-equilibrium plasmas as a function of the pressure, the excitation power and the argon content. In doing so, we have found that the argon upper energy levels used for electron temperature estimation remain close to corona bala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(65 citation statements)
references
References 32 publications
1
58
0
3
Order By: Relevance
“…2a)). It is worth mentioning that, in reasonable agreement with measurements of T e with increasing C 2 H 2 , the values of the T e associated with the Maxwellian fits (better for 20 % C 2 H 2 ) are roughly around 1.75 eV (for 1 % C 2 H 2 ) and the more realistic 1.15 eV (for 20 % C 2 H 2 ), exhibiting a decreasing trend with growing C 2 H 2 that is probably connected with an increase of the non-uniformly distributed [25,29] dust concentration in the discharge due to the fast polymerization of C 2 H 2 in the plasma. We can see in Figures 2 and 3 that the assumption of a Maxwellian shape for the EEDF is, in general, better justified as the relative concentration of C 2 H 2 grows so that the measured T e s are closer to the calculated ones when using 20 % C 2 H 2 .…”
Section: Study Of the Plasma: Oes And Analysis Of Eedfmentioning
confidence: 83%
See 3 more Smart Citations
“…2a)). It is worth mentioning that, in reasonable agreement with measurements of T e with increasing C 2 H 2 , the values of the T e associated with the Maxwellian fits (better for 20 % C 2 H 2 ) are roughly around 1.75 eV (for 1 % C 2 H 2 ) and the more realistic 1.15 eV (for 20 % C 2 H 2 ), exhibiting a decreasing trend with growing C 2 H 2 that is probably connected with an increase of the non-uniformly distributed [25,29] dust concentration in the discharge due to the fast polymerization of C 2 H 2 in the plasma. We can see in Figures 2 and 3 that the assumption of a Maxwellian shape for the EEDF is, in general, better justified as the relative concentration of C 2 H 2 grows so that the measured T e s are closer to the calculated ones when using 20 % C 2 H 2 .…”
Section: Study Of the Plasma: Oes And Analysis Of Eedfmentioning
confidence: 83%
“…The latter is only a useful approach since, under the conditions of this work (0.1 Torr, 300 W with an excitation frequency of 13.56 MHz), stochastic heating can also be important. [25] Therefore, although our approach of solving a homogeneous Boltzmann equation does not completely fit to the real physical situation of the problem, we believe that it is still valid and can give valuable information on the approximate behavior of the EEDF and mean electron energy in our dusty RF plasma. Moreover, recent results by Denysenko et al [31] have shown that, for relatively high dust density (∼5 × 10 7 cm -3 ) and/or dust radius (∼100 nm), the results of the homogeneous Boltzmann are reasonable in describing the effect of plasma nonuniformity on the EEDF.…”
Section: Study Of the Plasma: Oes And Analysis Of Eedfmentioning
confidence: 97%
See 2 more Smart Citations
“…The temperature of electron and the density of electron, etc.. By using the information from optical emission spectroscopy [13 -16]. The temperature of electron and the density of electron obtained by the following equation respectively: Reported by F.J. Vazquez et al the density of electron increasing and the temperature of electron decrease with increasing gas pressure , while electron temperature increase with increasing the power .Althought several studies have indicated to electrical characteristics of plasma , little attention has been paid to spectrum characteristics of plasma [17]. The aim of this research is to study the effect of changing applied voltage and working pressure on electron temperature , electron density and intensity of the spectral lines in argon plasma discharges to determine the optimum condition of produced plasma.…”
Section: Introductionmentioning
confidence: 99%